2015
DOI: 10.1111/fog.12105
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of jack mackerel landings (Trachurus murphyi) in central‐southern Chile through neural networks

Abstract: In the present study, the performance of neuronal networks models in monthly landing forecasting of jack mackerel (Trachurus murphyi) in central-southern Chile (32°S-42°S) was assessed. Thus, monthly estimations for 10 environmental variables, fishing effort (fe) and jack mackerel landings for the period 1973-2008 were used. A preliminary analysis was done in order to remove strongly correlated variables. Sea surface temperature (SST) and fe are established as input variables, then, a non-linear cross correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…On the other hand, ENSO variability seems to influence the spatial distribution of jack-mackerel, hence, affecting the catchability to the fishery (Yañez et al, 1996;Arcos et al, 2001;Naranjo et al, 2015). A similar finding was described for another jack mackerel species at New Zealand coasts, where ENSO variability has strong effects on krill distribution at coastal waters and introduce changes in the jack mackerel school behavior leading to fishery failures (Harris et al, 1992).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, ENSO variability seems to influence the spatial distribution of jack-mackerel, hence, affecting the catchability to the fishery (Yañez et al, 1996;Arcos et al, 2001;Naranjo et al, 2015). A similar finding was described for another jack mackerel species at New Zealand coasts, where ENSO variability has strong effects on krill distribution at coastal waters and introduce changes in the jack mackerel school behavior leading to fishery failures (Harris et al, 1992).…”
Section: Introductionmentioning
confidence: 76%
“…Indeed, Yañez et al (1996) reported that strong thermal gradients associated with the intrusion of oceanic waters off the Chilean coast increases the probability of catching jack mackerel, hence, influencing the operations of fishing vessels. For example, Chilean fishing fleet increased it capacity (larger vessels), the duration of the fishing trips and number of hauls per trip in response to changes in jack mackerel spatial distribution (Naranjo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Naranjo et al . () presented a set of models based on neuronal networks to forecast jack mackerel landings ( Trachurus murphyi ) in central southern Chile. For jack mackerel, anthropogenic effects (e.g.…”
Section: Climate Variability and Change Impacts On Marine Resources Amentioning
confidence: 99%
“…This supplement presents two articles related to this major theme, both exploring the use of environmental variables to forecast landings. Naranjo et al (2015) presented a set of models based on neuronal networks to forecast jack mackerel landings (Trachurus murphyi) in central southern Chile. For jack mackerel, anthropogenic effects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence models, specifically deep learning models (DLM), are characterized by their ability to predict a variable's value concerning a specific scenario (Zhang et al 2018). The DLM have been used to forecast the catches of different fisheries, like mackerel, cod, sardine or finfish (Kim et al 2015, Naranjo et al 2015, Kim et al 2016, Petatán-Ramírez et al 2019. DLM has used as input variables of different data types, such as satellite images of sea spectrograph (e.g.…”
Section: Introductionmentioning
confidence: 99%